Analisis Risiko dan Strategi Keamanan dalam Jaringan Peer-to-Peer (P2P) dan Jaringan dengan Internet of Everything (IOE) untuk Smart Campus (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2025)
Digital transformation within campus environments through the integration of Peer-to-Peer (P2P) networks and the Internet of Everything (IoE) offers high efficiency and intelligent connectivity, yet introduces significant challenges regarding network security and vulnerability risks. This study aims to analyze these risks and design contemporary technology-based security strategies to support Smart Campus systems. Utilizing a Research and Development approach, a hybrid security model was developed based on adaptive encryption technologies and AI-driven monitoring. Experimental results demonstrate a 72% increase in threat detection capabilities and an average attack mitigation response time of 3.4 seconds.